2023
DOI: 10.1088/1748-9326/ace273
|View full text |Cite
|
Sign up to set email alerts
|

Arctic amplification has already peaked

Abstract: It has been demonstrated that the Arctic has warmed at almost four times the global average rate since 1979, a phenomenon known as Arctic amplification. However, this rapid Arctic warming is tightly linked to the retreat and thinning of summer sea ice, and so may be expected to weaken as the Arctic transitions to seasonal ice cover. Here we show evidence from gridded observations and climate reanalysis that Arctic amplification peaked sometime in the early 2000s. This occurred concurrently with a maximum in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Using the mean global temperature projected by the CMIP6 ensemble mean (solid black curve in Figure 3d), the AA up to 2050 is limited to values between 2 and 3. A similar result was recently reported by Davy and Griewank (2023).…”
Section: Future Aa Projectionsupporting
confidence: 92%
“…Using the mean global temperature projected by the CMIP6 ensemble mean (solid black curve in Figure 3d), the AA up to 2050 is limited to values between 2 and 3. A similar result was recently reported by Davy and Griewank (2023).…”
Section: Future Aa Projectionsupporting
confidence: 92%
“…Speci cally, Dai et al (2019) showed that AA weakens in model experiments with 1%/year CO 2 increases and xed SIC for surface ux calculations, and that negligible additional AA will occur after sea-ice completely melts away. Davy and Griewank (2023) con rmed this nding by showing that as the rate of sea-ice loss decreases in the future, concurrent AA weakens.…”
Section: Introductionmentioning
confidence: 63%
“…Lastly, our results from the highest emission scenario suggest that AA is expected to continue at a rate more than twice as global average, even under the likelihood of seasonally ice-free conditions by mid-century. However, AA is unlikely to be as strong as in the early 2000s, where a peak value has been identified contemporaneous with a peak in sea ice loss (Davy and Griewank 2023). Again, this concurrent occurrence of peaking AA and sea ice loss hints to the crucial role of ice melt for the evolution of AA, and further suggests that if sea ice melts away entirely, the sea-ice control on the evolution of AA diminishes.…”
Section: Discussionmentioning
confidence: 96%